Assessment of the effectiveness of DOST RSTL-Davao Microbiology Laboratory Services to the Food Industry in Region XI - Napoco, Sheryl Narida; Cruz, Edson (Quezon City University of the Philippines Diliman, 2012)
The DOST RSTL-Davao Microbiology Laboratory has a vision to become a world-class organization through its internationally certified quality systems. The Chemistry Laboratory, Microbiology Laboratory and Metrology and Calibration Laboratory of DOST-Regional Standards and Testing Laboratory (RSTL) Davao are an ISO/IEC 17025 accredited. This study assessed the effectiveness of the services of microbiology laboratory to the food industry, identified the problems of the laboratory's operation, recommended areas for improvement, and evaluated if there is a need to establish more microbiology facilities. The research design of this study consisted of three phases of an operational framework called Microbiology Service Improvement Program (MSIP). The empirical research component of this study is basically descriptive in nature wherein a comparison between the results of the SWOT analysis and the CSM results was performed in order to identify the factors that affect the effectiveness of the laboratory. The study revealed that DOST RSTL-Davao Microbiology Laboratory has been effective in delivering services to the food industry despite the manpower shortage which resulted to long scheduling of tests analyses. Based on the 80 percent CSI of the DOST RSTL-Davao Microbiology Laboratory, the rating has met the 75 percent target CSI established by RSTL and has 80 percent been successful in satisfying its customers in the food industry based on the 22 microbiology analyses features presented in the CSM questionnaire. The rating also is a testimony of the DOST RSTL-Davao top management's commitment to customer satisfaction. The revenue contribution of microbiology laboratory has a great impact on the DOST-RSTL Davao's target income whose yearly actual income surpassed its target income by an average of 10 percent. One of the strengths of the laboratory is its ISO/IEC 17025 accreditation from PAO. The laboratory boasts of competent, trained and experienced personnel who have gained the confidence and trust of regular customers. Since 2005 up to the present, the laboratory has maintained a quality system and the technical competence to meet the microbiological requirements of the food industries in order to sustain their competitiveness in terms of quality products and productivity. As result of the SWOT analysis, there are many identified weaknesses of the microbiology laboratory which hamper its efficient operations and maintenance. The RSTL Davao's lack of manpower causes the long scheduling of tests analyses required by the customers and may sometimes causes clients to transfer to other laboratories that could cater the tests the soonest time possible. The lack of marketing activities makes customers unaware of the full capabilities of the microbiology laboratory and the lack of incentive schemes lessens the motivation and self-esteem of the personnel to perform voluminous tests requests from the customers. Using the reliable results of the CSM survey conducted from January to February 2012, the overall service quality gap of -0.127 means that the laboratory did not meet the expectations of the customers based on their perceptions of the DOST RSTL-Davao Microbiology Laboratory's performance and facilities. The laboratory has to make some improvements particularly in the eight (8) features identified with the highest gap in the CSM. These areas are the appearance and value of the microbiology laboratory's physical facilities, communication materials such as service brochures, and quality policy, laboratory fees and the laboratory's ability to perform the promised service dependably and accurately. Moreover, the long scheduling of tests analyses and the lack of marketing activities are the areas where DOST RSTL-Davao Microbiology Laboratory should make better results. From the SWOT analysis, turning the weaknesses to strengths and enhancing the opportunities in order to minimize the threats of the business can also be considered as areas for improvement. Although adopting all of them as PFIs is feasible, several factors have to be considered in order to come up with the most positive business impact by adopting PFIs that will generate the greatest possible gains in customer satisfaction at the lowest possible cost. There were identified areas for improvement and there is a need to set up more microbiology facilities to serve the requirements of the industry. Lastly, the study offered some recommendations deemed necessary to enhance the services of the laboratory.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Food industry and trade -- Philippines; Administrative agency -- Department of Science and Technology -- Philippines; Microbiology laboratory services; Microbiology Service Improvement Program